Diving ergospirometry with suspended weights: breathing- and fin-swimming style matter - Andreas Koch; Dennis Kramkowski; Mattes Holzum; Wataru Kähler; Sebastian Klapa; Bente Rieger; Burkhard Weisser; Jochen D. Schipke (European Journal of Applied Physiology, 2022)
Purpose Scuba diving is a complex condition including elevated ambient pressure, limited air supply, increased breathing work, and unfamiliar fin-swimming. Earlier approaches to assess diving specific data did not comprehensively address these aspects. We first present an underwater ergospirometry system and then test the hypothesis that both breathing characteristics and fin-swimming style affect the air consumption. Methods/Participants A suspended-weights ergospirometry system was mounted inside a hyperbaric chamber. Ergo group: 25 divers (24.6 ± 4.1 years); three set-ups: dry normobaric cycling (75–225 W), dry cycling at 20 m simulated depth (75–225 W), fin-swimming at 20 m (5–8 kg suspended weights). Style group: 20 other divers (24.6 ± 4.1 years): fin-swimming at 20 m (5–8 kg) with regard to ventilation ( $$\dot{V}$$ V ˙ E) and fin-swimming style. Results Ergo group: linear heart rate and oxygen uptake ( $$\dot{V}$$ V ˙ O 2 ) increases with both 50 W-bicycle steps and suspended-weights ergometry ( r = 0.97). During hyperbaric conditions, $$\dot{V}$$ V ˙ E was less increased versus normobaric conditions. Style group: the more efficient hip/thigh-oriented style shifted towards the knee/calf-oriented style. $$\dot{V}$$ V ˙ E and $$\dot{V}$$ V ˙ O 2 were higher in beginners (< 100 dives) versus advanced divers (≥ 100 dives). Significant differences on the 5 kg-step: $$\dot{V}$$ V ˙ E: 31.5 ± 7.1 l/min vs. 23.7 ± 5.9 l/min and $$\dot{V}$$ V ˙ O 2 : 1.6 ± 0.3 l/min vs. 1.2 ± 0.3 l/min. A comparison is presented, in addition to illustrate the impact of differences in breathing characteristics and fin-swimming style. Conclusions Diving ergospirometry with suspended weights in a hyperbaric chamber allows for comprehensive studies. Little diving experience in terms of breathing characteristics and fin-swimming style significantly increases $$\dot{V}$$ V ˙ E thereby increasing the risk of running-out-of-air.